2023
DOI: 10.1108/imds-08-2022-0500
|View full text |Cite
|
Sign up to set email alerts
|

The effects of AI service quality and AI function-customer ability fit on customer's overall co-creation experience

Abstract: PurposeThe application of artificial intelligence (AI) in the customer market has completely changed customer behaviors. This study aims to investigate the customers' co-creation experiences with AI in the digital age.Design/methodology/approachAn online survey was used to collect data from 699 customers who had used AI-enabled banking services. Hypotheses were validated using partial least squares modeling.FindingsThe findings indicate that the customer response capabilities (e.g. perceived response expertise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 83 publications
0
8
0
1
Order By: Relevance
“…Managerial attitudes towards the technology (metaverse, IMT) facilitating this conversion, their willingness to take risks (Zhang et al, 2023) and their own interest in MVM (Ramadan, 2023) all have an effect on how organisational processes are changed to take advantage of the transition from CI to SA. Yang (2023) contends that customer reaction capability (CRC) is an essential part of management capability and takes the form of response expertise and response time to CI determinants such customer engagements, customer knowledge acquisition and assimilation, and presence. This gives information about what kinds of products and services customers want, and it also encourages the development of customer experience management and value co-creation that are compatible with market dynamics.…”
Section: Moderating Role Of Managerial Capabilities On the Relationsh...mentioning
confidence: 99%
“…Managerial attitudes towards the technology (metaverse, IMT) facilitating this conversion, their willingness to take risks (Zhang et al, 2023) and their own interest in MVM (Ramadan, 2023) all have an effect on how organisational processes are changed to take advantage of the transition from CI to SA. Yang (2023) contends that customer reaction capability (CRC) is an essential part of management capability and takes the form of response expertise and response time to CI determinants such customer engagements, customer knowledge acquisition and assimilation, and presence. This gives information about what kinds of products and services customers want, and it also encourages the development of customer experience management and value co-creation that are compatible with market dynamics.…”
Section: Moderating Role Of Managerial Capabilities On the Relationsh...mentioning
confidence: 99%
“…Research has shown that AI can be an impactful tool for customer co-creation experiences. For example, Yang (2023) shows that when customer co-creation with AI is part of a firm's strategy, poor AI function-customer fit can negatively impact the impression of the relationship between AI service quality and the overall co-creation experience. AI is often used to customize service delivery (both online and offline), where AI can personalize services based on customer data, strengthening the customer-firm relationship (Kumar et al, 2019).…”
Section: Ai and Customer Experiencesmentioning
confidence: 99%
“…Understanding how AI integration in customer communities influences customer behavior, both within and outside the community, is AI in online customer communities another potential area for future research. We can say that it is essential to investigate the distinctive behavioral patterns that manifest and interact with factors such as user satisfaction, interaction frequency and the generation of user-created content (Perez-Vega et al, 2021;Yang, 2023). Understanding the intricate connections between these behavioral patterns and user experience elements is critical to optimizing the effectiveness of AI integration in such communities.…”
Section: Future Research Agendamentioning
confidence: 99%
“…Third, another gap is that many extant studies are based on traditional technology adoption and related models and do not focus on the user's engagement and experience standpoint. The technology enabled value creation research stream requires a contemporary perspective, such as a service-dominant (SD) logic framework (Vargo and Lusch, 2004), to understand consumer engagement and value co-creation (Manser Payne et al, 2021; IMDS 124,2 Apostolidis et al, 2021;Winkler and Wulf, 2019;Yang, 2023). In addition, there is a growing call for a rethinking of the co-creation process with technology (Li et al, 2021;Yang, 2023).…”
Section: Mobile Business Apps 859mentioning
confidence: 99%
“…The technology enabled value creation research stream requires a contemporary perspective, such as a service-dominant (SD) logic framework (Vargo and Lusch, 2004), to understand consumer engagement and value co-creation (Manser Payne et al, 2021; IMDS 124,2 Apostolidis et al, 2021;Winkler and Wulf, 2019;Yang, 2023). In addition, there is a growing call for a rethinking of the co-creation process with technology (Li et al, 2021;Yang, 2023). Finally, another gap in the literature is that the bulk of the extant quantitative studies dealing with mobile business apps (see Gurtner et 2014;Legner et al, 2016;Lee, 2016) focus on simple direct effects and indirect effects.…”
Section: Mobile Business Apps 859mentioning
confidence: 99%